Innovative Business Models in the Tennis Industry: A Literature Review - Hakim, Hikmad; Ishak, Muhammad (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This study aims to analyze innovative business models in the tennis industry through a literature review of 25 articles published between 2015 and 2025. The research method uses a literature review approach with a search process through international and national databases such as Scopus, Google Scholar, Web of Science, DOAJ, SINTA, and Garuda. Studies that meet the criteria are analyzed using thematic analysis and narrative synthesis techniques, supported by descriptive statistics to see the trends of the findings. The results of the study indicate six main themes that dominate the development of tennis business models, namely: business model innovation, digitalization and technology utilization, service design and customer experience, revenue diversification, governance and management, and global trends in the sports industry. Quantitative analysis of 10 studies shows that the implementation of innovation has a significant impact on tennis club performance, including an increase in revenue of 44.8%, an increase in the number of new members of 40.5%, an increase in member retention of 27.4%, and an increase in customer satisfaction of 37.5%. These findings confirm that transforming a business model from a traditional approach to a digital-based model, with value-added services, and a sport-lifestyle strategy is a strategic step to increase the competitiveness and sustainability of tennis clubs in the modern sports industry. Therefore, this research contributes to the development of sports management theory and serves as a practical reference for managers and stakeholders in designing an adaptive, innovative, and sustainable tennis business model